INFLUENCE OF ARBUSCULAR MYCORRHIZAL FUNGI AND SOIL AMELIORANTS ON THE MYCORRHIZAL COLONIZATION, CHLOROPHYLL CONTENT, AND PERFORMANCE GROWTH OF TWO TROPICAL TREE SEEDLINGS GROWN IN SOIL MEDIA WITH HIGH ALUMINUM CONTENT - BUDI, SRI WILARSO; ARTY, BUDI; WIBOWO , CAHYO; SUKENDRO, ANDI (Malaysian Applied Biology, 2020)
Aluminum is one of heavy metals and its availability is correlated with low soil pH, such as in acidic soil as well as post mining soil and become limiting factors for plant growth. MycoSilvi is a biofertilizer inoculant product containing arbuscular mycorrhizal fungi enriched with Mycorrhizal Helper Bacteria’s (MHBs) designed for improving plant growth on post-mining soil media with low pH and high aluminum content. This study was conducted to determine the potential use of three variants of MycoSilvi, both single or in combination with soil ameliorant to enhance Albizia chinensis (Osbeck) Merrill and Pongamia pinnata (L.) Pierre growth. This study was conducted by randomized complete design with factorial scheme in a greenhouse for 4 months. The first factor consisted of four different levels based on MycoSilvi (M) inoculation: control (M0); MycoSilvi variant 1 (M1), MycoSilvi variant 2 (M2) and MycoSilvi variant 3 (M3). The second factor consisted of four levels based on the addition of lime and compost to soil medium: control (L0C0), addition of lime (L1C0), addition of compost (L0C1) and addition of lime and compost (L1C1). Data was analyzed using analysis of variance (ANOVA). Total chlorophyll content as indicated by leaf greenness index, height, steam diameter, biomass, root colonization and P accumulation on both plant species were observed after 12 weeks of planting. The results showed that the MycoSilvi inoculation differently colonized the roots and increased P uptake, leaf greenness index and growth of both plants species. The addition of lime and compost increased the mycorrhizal roots colonization, P uptake, leaf greenness index and plant growth of both plants’ species. The best result was obtained from the combination treatment of MycoSilvi variant 3, lime and compost